Regulation of angiogenesis by a non-canonical Wnt-Flt1 pathway in myeloid cells - Stefater, James A. (2011)
Myeloid cells are a feature of most tissues. Here we show that during development, retinal myeloid cells (RMCs) produce Wnt ligands to regulate blood vessel branching. In the mouse retina, where angiogenesis occurs postnatally(1), somatic deletion in RMCs of the Wnt ligand transporter Wntless(2,3) results in increased angiogenesis in the deeper layers. We also show that mutation of Wnt5a and Wnt11 results in increased angiogenesis and that these ligands elicit RMC responses via a non-canonical Wnt pathway. Using cultured myeloid-like cells and RMC somatic deletion of Flt1, we show that an effector of Wnt-dependent suppression of angiogenesis by RMCs is Flt1, a naturally occurring inhibitor of vascular endothelial growth factor (VEGF)(4-6). These findings indicate that resident myeloid cells can use a non-canonical, Wnt-Flt1 pathway to suppress angiogenic branching.